Against borders : promoting books for a multicultural world - Rochman, Hazel (American Library Association, 1993)
This excellent work addresses the issues and controversies surrounding multicultural literature. Rochman, who lived under apartheid in South Africa and who is assistant editor for Booklist's youth section believes that books make a difference, Her introduction attempts to put multiculturalism in perspective, The first half of the book consists of thematic essays about literature and culture with examples drawn from a variety of literary works. The second half is an annotated bibliography of fiction, nonfiction and videos about the Holocaust, apartheid, ethnic groups in the United States and issues from other regions around the world. There is a thematic index to the books mentioned in the essays, and a general author-title index. Highly recommended for all secondary schools, for selection, reading guidance and unit planning.